Answers

2016-07-09T20:44:27+08:00
For example, 

a. The unknown is a1

35 = a1 + (6-1)5

Here, the 6th term is 35, the common difference is 5 and we have to find the first term

35 = a1 + 5(5)
35 = a1 + 25
35-25 = a1
10 = a1

b. The unknown is an 

an = 5 + (7-1)3

Here the first term is 5, the common difference is 3 and we have to find the 7th term

an = 5 + (6)3
an = 5 + 18
an = 23

3. The unknown is d

60 = 10 + (6-1)d
 
Here 60 is the 6th term, 10 is the first term and we have to find the difference.

60 = 10 + 6d - d
60 = 10 + 5d
60 - 10 = 5d
50 = 5d
50/5 = 5d/5
10 = d
1 5 1